PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA PEGAWAI BADAN PERLINDUNGAN PEKERJA MIGRAN INDONESIA - Chelsi Sinaga; Siwi Nur Indriyani (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2025)
To determine the effect of workload and work stress on the performance of the emplyoyees migrant worker protection agency. The analysis model used is linear regression both simply and Simultaneously.The results of the study indicate that workload has a positive and significant effect on the performance of employees at the Indonesian Migrant Workers Protection Agency, while work stress has a negative and insignificant effect on the performance of employees at the Indonesian Migrant Workers Protection Agency. Simultaneously, workload and work stress have a positive effect on the performance of employees at the Indonesian Migrant Workers Protection Agency